Human Amniotic Fluid Stem Cell In Vitro Inhibits Colon Cancer Cell Growth - Phermthai, Tatsanee; Wichitwiengrat, Suparat; Tongbopit, Sasiprapa; Reaugpracha, Athisek (Thai Journal of Toxicology, 2020)
Colon cancer is a common malignant tumor that ranked in a group of the top ten reading cancers in Thailand. Recently, it was reported that mesenchymal stem cells (MSC) can inhibit cancer cell growth in experimental animals. Thus, human amniotic fluid stem cell (hAFSC), a kind of MSC, may show similar effect for inhibiting cancer cell growth. The aims of present study were to investigate the effects of hAFSC on colon cancer cell line (HT29 growth when these two cells were co-cultured for 24 hours. Our study was divided into 2 experiments. The first experiments was to examine the morphological appearances of HT29 cell that co-culture with hAFSC at ratio 1:1 (HT29 3000 cells:hAFSC 3000 cells) and 1:3 (HT29 3000 cells:hAFSC 9000 cells), while the second experiment was to evaluate the changes in HT29 cell number after co-culture with hAFSC at ratio 1:1 and 1:3 as well. The results showed that morphological appearances of HT29 cell were changes after co-cultured with hAFSC by losing its round shape colony forming ability as compared to the controls (HT29 cell alone). The forming colony of HT29 cell in the co-culture group was dispersed and laid in monolayer pattern. In addition, morphological appearances of HT29 cell were increased as the number of hAFSC was increased. Moreover, we found that the changes in HT29 cell number after co-culture with hAFSC were decreased higher when the hAFSC cell number was increased. The results of our preliminary study suggest that hAFSC has the ability to inhibit colon cancer cell growth.